SISTEM PENDUKUNG KEPUTUSAN PEMBERIAN KREDIT MENGGUNAKAN METODE SIMPLE MULTI ATTRIBUTE RATING TECHNIQUE EXPLOITING RANK (SMARTER) PADA PT PERMODALAN NASIONAL MADANI (PNM) KOLAKA UTARA - Arlingga Vanega Nurdin; Sutardi Sutardi; Ika Purwanti Ningrum (semanTIK, 2019)
The Decision Supporting System, known as DSS is part of a computer-based information system. DSS is expected to provide information that would provide an alternative solution to the problem that occurred. PT. Permodalan Nasional Madani through MMSU (Micro Model Service Unit), a product which was launched to bridge the limitation of customers in gaining access to credit decision. But in fact, there are some factors that hinder the process of granting credit financing facility to customers. The decision supporting system which is developed by the Writer is an application that can facilitate decision-making of granting credit in accordance with predefined criteria authorities in PT. Permodalan Nasional Madani North Kolaka branch using the Simple Multi-Attribute Rating Technique Exploiting Rank (SMARTER) method. This method is a method of comparing the criteria to reference criteria in order to find the value of the feasibility of each profile existing data. In the process of employee assessment using two criteria which consists of 5 sub-criteria and 15 sub-sub-criteria. The decision-making process of granting credit can be done quickly, accurately and in accordance with the criteria used in order to minimize the time. The result of the decision system generated by ranking the results of the feasibility form the highest to the lowest.Keywords—DSS, Credit Granting, SMARTER DOI : 10.5281/zenodo.3243149